Pre-Service Teachers' Perceptions of the Contributions of Field Trips on Climate Change Education - Yuliyanto, Eko; Supriyanto, Supriyanto (Yayasan Keluarga Guru Mandiri, 2025)
Numerous methodologies have been employed to enhance competencies in climate change education. However, applying and systematically evaluating field trips as a pedagogical approach in climate change education must be explored. It is essential to explore pre-service teachers' perceptions regarding the impacts of their participation in field trips. This study evaluated the significant changes observed in pre-service teachers following field-trip-based learning. The field trip program was evaluated using the Most Significant Change (MSC) evaluation model. The results identified several themes of substantial changes in pre-service teachers. This study concludes that field trip-based learning facilitates positive transformations in pre-service teachers, as evidenced by their favorable responses following the field trip and their reflective insights on the conceptual understanding of climate change. This research contributes to scientific understanding by demonstrating that sea level rise, which has led to the submergence of villages along the northern coast of Java, serves as a valuable contextual framework for field trips to study the impacts of climate change. In recognition of the limitations, future research should broaden its scope to include field trip activities in diverse geographical settings.